The Risk Preferences Of Graduates Of Islamic Educational Institutions In Indonesia - Salahuddin Rijal Arifin; Dimas Herliandis Shodiqin; Iftitah Rita Udiniyah; Fajri Yuriz Habibi (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Indonesia as a Muslim-majority country and the survey results show that the most Indonesian are religious. Religious education also gets facilities from the state as a form of support for people's needs for religion. Religiosity, and education are hypothesized to be determinants of risk preference. This study aims to uncover the relationship between risk preferences and Islamic faith-based education in the Indonesian context. This research tries to combine aspects of religiosity and educational aspects in one framework, namely Islamic faith-based education where previous studies do not unite aspects of religiosity and education. This research is expected to provide a more complete picture or map of the risk preferences of graduates of Islamic educational institutions.